Multilevel Associations of Food Environment and Papillary Thyroid Cancer Outcomes in the United States - David J. Fei‐Zhang; Eric Pan; Jean‐Nicolas Gallant; Andrés M. Bur; Ryan H. Belcher (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Objective To assess the independent associations of poor food environment with differences in papillary thyroid carcinoma (PTC) outcomes using the United States Department of Agriculture (USDA)‐validated Food Environment Atlas (FEA). Methods This retrospective cohort study assessed patients from 2000 to 2017 for trends in overall and 3‐year survival, and the number of tumors at diagnosis with increasing food environment vulnerability/FEA‐scores by Cox hazards and logistic regression models stratified by race‐ethnicity and age. FEA‐scores were based on 282 county‐level variables of food security, store‐restaurant availability, SNAP/WIC enrollment, pricing, taxes, and producer vicinity while adjusting for traditional social determinant factors. Results Among 148,296 patients, increased food environment vulnerability was associated with decreased overall survival (HR 1.06, 95% CI 1.04–1.07). These FEA effects were exacerbated among non‐White patients (1.08, 1.05–1.11) compared to White patients (1.05, 1.04–1.07). Increased FEA was also associated with increased 3‐year mortality (OR 1.05, 95% CI 1.03–1.07). These effects were exacerbated among non‐White (1.06, 1.02–1.10) and older patients (1.05, 1.02–1.07). Increased food environment vulnerability was additionally associated with increased odds of having more than one primary tumor (1.02, 95% CI 1.01–1.03). When stratified separately for race and for age, worse food environment was associated with non‐White patients (1.03, 1.01–1.06) and patients aged 45 years and older (1.02, 1.01–1.03). Conclusions Food environment vulnerability was associated with poorer prognosis after adjusting for traditional social determinant vulnerabilities, with varying magnitude upon stratification of race and age. Given PTC's rise in incidence and severity, the effects of food environment should be considered when informing future investigation and policy. Level of Evidence III